Optimizing Student Interest in Social Studies Through the Integration of Project-Based Learning and Wordwall Media in the Topic of Social Integration - Adelia Zhakila Ramadhani; Silvi Nur Afifah; Dian Ayu Larasati; Sugiantoro Sugiantoro (Pusdikra-Publishing.com, 2026)
Low student interest in Social Studies (IPS) remains a common issue in the school learning process. Instruction dominated by lecture-based methods often results in students being passive and lacking interest in learning activities. This study aims to analyze the impact of implementing Project-Based Learning (PjBL) supported by Wordwall media on the learning interest of eighth-grade students at SMP Negeri 9 Surabaya regarding the topic of Social Integration. The study employed a quantitative approach using a quasi-experimental method with a Nonequivalent Control Group Design. The sample consisted of 35 students in the experimental class and 36 students in the control class. Data collection techniques included learning interest questionnaires, observation, and documentation. Data analysis involved descriptive statistics, normality tests, homogeneity tests, and an Independent Sample t-Test. The results showed that the average learning interest in the experimental class (3.02) was higher than that in the control class (2.71). Hypothesis testing yielded a significance value of 0.037 (p < 0.05), indicating a significant effect of PjBL supported by Wordwall on student learning interest. Furthermore, students responded positively to the instruction, finding it engaging, interactive, and capable of enhancing their involvement in the learning process. Thus, integrating PjBL with Wordwall serves as an effective alternative for Social Studies instruction to boost student learning interest.